1985
DOI: 10.1016/s0022-5347(17)47033-9
|View full text |Cite
|
Sign up to set email alerts
|

Inguinal Lymph Node Metastases from Testicular Tumor

Abstract: The Northern Israel Cancer Center serves 1 million inhabitants. Between 1968 and 1982, 33 patients with a diagnosis of nonseminomatous tumors of the testis were referred to this center. Of these patients inguinal lymph node metastasis developed in 4, each of whom had had risk factors for such metastasis. Two patients had undergone previous orchiopexy, and 2 had extension of the tumor to the epididymis and the tunica vaginalis testis. The inguinal region should be examined and watched carefully in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Various studies analyzed the factors associated with postoperative complications and hernia recurrence (15). In about 2% of cases testicular cancer lymphatic metastatization is atypical and includes inguinal lymph nodes (1)(2)(3)(4). This unusual lymphatic spreading may happen for a significant variation of an otherwise normal anatomical pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies analyzed the factors associated with postoperative complications and hernia recurrence (15). In about 2% of cases testicular cancer lymphatic metastatization is atypical and includes inguinal lymph nodes (1)(2)(3)(4). This unusual lymphatic spreading may happen for a significant variation of an otherwise normal anatomical pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The anatomy of lymphatic drainage from the testis and scrotum is well described and mechanisms of dissemination to inguinal nodes are very well documented in patients with previous surgery in the inguinal region [3][4][5][6][7][8][9]. Klein et al [5] reported 22 cases of testicular cancer with inguinal node metastases diagnosed between 1948 and 1982.…”
Section: Discussionmentioning
confidence: 99%
“…Significant variation in this 'regular' anatomical pattern can be created by surgical violation of the scrotum or inguinal region (orchidopexy, relief of hydrocele, trans-scrotal biopsy or varicocelectomy) [3][4][5][6][7][8][9], by extension of the tumour through the testicular capsule or invasion into the epididymis [7]. These patients can develop direct lymphatic drainage to the inguinal nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Reports that previous scrotal surgery predisposes to inguinal node metastases (Witus et al, 1959;Bowles, 1962;Stein et al, 1985) supported recommendations for hemiscrotectomy and en bloc removal of the spermatic cord and ilio-inguinal nodes for non-seminomatous tumours, or in seminoma for the inclusion of the area in the radiotherapy field (Doornbos et ul., 1975). In a series of 14 patients with non-seminomatous tumours occurring after previous scrotal surgery, treated with chemotherapy and retroperitoneal lymphadenectomy or chemotherapy alone, no patient was found to develop inguinal lymph node metastases (Lanteri et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Scrota1 biopsy of testicular tumours was considered to carry an even graver risk of local recurrence (Dean, 1925). Previous scrotal surgery such as orchiopexy (Witus et ul., 1959;Stein et al, 1985), varicocelectomy (Bowles, 1962) and exploration for torsion altered scrotal lymphatic drainage so as to predispose to dissemination via the inguinal lymphatics. In the absence of scrotal violation the risk of local recurrence of the disease has been considered minimal (Whittle, 1957).…”
Section: Testicular Tumour Unit Royal Marsden Hospital London and Smentioning
confidence: 99%